International Osteoporosis Foundation and International Federation of Clinical Chemistry and Laboratory Medicine position on bone marker standards in osteoporosis. - Vasikaran, S; Cooper, C; Eastell, R; Griesmacher, A; Morris, H; Trenti, T; Kanis, J (2011)
The International Osteoporosis Foundation (IOF) and the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) Working Group on Bone Marker Standards (WG-BMS) has evaluated the clinical potential of bone turnover markers (BTMs) in the prediction of fracture risk and for monitoring treatment. Research evidence suggests that BTMs may provide information on fracture risk independently from BMD, so that fracture risk prediction might be enhanced by their inclusion in assessment algorithms. The potential use of BTMs to predict the response to treatments for osteoporosis in the individual patient is also of great interest. Treatment-induced changes in specific markers account for a substantial proportion of fracture risk reduction. However, there is still a need for stronger evidence on which to base practice in both situations. IOF/IFCC recommends one bone formation marker (serum procollagen type I N propeptide, s-PINP) and one bone resorption marker (serum C-terminal cross-linking telopeptide of type I collagen, s-CTX) to be used as reference markers and measured by standardised assays in observational and intervention studies in order to enlarge the international experience of the application of markers to clinical medicine and to help resolve uncertainties over their clinical use.